Integrated assessment of yam mosaic virus (YMV) resistance in wild‑yam (Dioscorea spp.) interspecific cross progenies using field phenotyping, molecular, and biotechnological approaches - Oyedoyin, F.P.; Kolade, O.; Agre, A.P.; Olawuyi, O.J.; Kumar, P.L.; Asfaw, A. (2025)
Yams (Dioscorea spp.) are important food crops for millions in tropical and subtropical regions. Yield loss due to Yam Mosaic Virus (YMV genus Potyvirus) has been reported to have a high level of damage, especially on white Guinea yam (D. rotundata). Crop wild relatives often serve as potential sources of alleles that are absent in many cultivated crop species, howevertheir potential for source new disease resistance alleles in yam plants remains underexplored. Therefore, this study evaluated YMV resistance in interspecific hybrids derived from two wild yam specieses, Dioscorea abyssinica as female parent and Dioscorea praehensilis as male parent, for trait introgression. Sixty-five wild yam hybrid genotypes and their parents (maternal-TDabwild and paternal-TDPr 1018) were planted on the field exposed to natural infestation. Field phenotyping and disease severity ratings (1- asymptomatic, 2- resistant, 3- moderately resistant, 4- susceptible and 5- highly susceptible) were combined with molecular analyses using three diagnostic SNP markers, Biotechnology tool ELISA, and RT-PCR to predict, detect and quantify YMV disease resistance and susceptibility patterns. Significant variability in disease resistance was observed, with hybrids exhibiting a wide range of area under disease progress curve (AUDPC) values. Genotypes with the lowest AUDPC values (63) displayed enhanced resistance, while those with higher values (197–231) were more susceptible, reflecting a higher overall disease impact. The ELISA and RT-PCR findings further revealed diverse responses to YMV among the progenies and parents. Two markers, snpDR00160 and snpDR00162, displayed favourable resistant alleles GG and AA, respectively, and susceptible allele TT while marker snpDR00161 failed to amplify across all the progenies. Six progenies (TDabp2101007, TDabp2101009, TDabp2101015, TDabp2101021, TDabp2101026, and TDabp2101060) together with the male parent (D. praehensilis -TDPr 1018) demonstrated putative resistance across phenotypic, molecular, and biotechnological assessments, making them as promising candidates for yam breeding programs aimed at developing YMV-resistant cultivars.